Guest commentary: a review and framework for studying the repatriation experiences of Malaysian Faculty - Hunt, David Marshall; Rohayu Abdul-Ghani (Penerbit Universiti Kebangsaan Malaysia, 1998)
The repatriation process often is assumed to be an easy one when in fact it is not. The literature on repatriation is predominantly Western; therefore, this issue needs further examination as it pertains to people of all nationalities. A framework for further systematic study of developing nation expatriates is presented together with some preliminary results of an exploratory nature, based on extensive interviews and questionnaire data gathered on seven Malaysian faculty. We present these results in the form of a composite case to protect confidentiality of our small sample of subjects. Our focus is on reverse culture shock upon repatriation. We conclude with a reminder that this is exploratory research, and as such has several limitations, and with some suggestions for a more systematic approach to future research on repatriation.